Selective Internal Radiation Therapy for Gastrointestinal Neuroendocrine Tumour Liver Metastases: A New and Effective Modality for Treatment - Harshal Rajekar; Kashan Bogammana; Richard S. Stubbs (International Journal of Hepatology)
Background. Nonresectable neuroendocrine tumour (NET) liver metastases respond poorly to most widely available and used therapies. Selective Internal Radiation Therapy (SIRT) is becoming recognized as a new modality for selectively treating non-resectable liver tumours. This paper presents an experience of 14 patients with non-resectable NET liver metastases treated with SIRT. Methods. Between September 1997 and October 2009 14 patients with extensive NET liver metastases were treated with 2.0 to 3.0 GBq of 90Yttrium microspheres. Repeat SIRT was undertaken in three patients after 16, 27, and 48 months, respectively. Responses were assessed clinically, biochemically, and with serial CT scans. Survival was measured from initial SIRT. Results. Some response was seen in all 14 patients. Carcinoid syndrome improved or resolved in 10/10 instances. 24-hour urinary 5-HIAA or serum chromogranin A levels fell dramatically in 5/7 patients following SIRT. Serial CT scans revealed partial response or stable disease in all 14 patients. Repeat treatment in three patients experiencing progression was associated with a further response. Median survival after SIRT is 25 months with 6 patients being alive (and 3 patients still asymptomatic), at 19, 22, 23, 23, 58, and 60 months. Conclusions. SIRT is an effective and well-tolerated treatment for non-resectable NET liver metastases capable of both alleviating the carcinoid syndrome and achieving significant tumour regression. Repeat treatment is an option and liver resection after downstaging may also become possible.